2014
DOI: 10.5664/jcsm.4038
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Measures Predict Next-Day Symptoms in Women with Irritable Bowel Syndrome

Abstract: This small exploratory study supports previous findings that self-reported sleep disturbance predicted exacerbation of next-day symptoms in women with IBS and extends this relationship using an objective sleep measure. The study adds further evidence that sleep quality predicts subsequent IBS symptoms, but not the converse. The findings from this small study support the importance of additional longitudinal research to further understand the relationships between sleep and IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 31 publications
2
67
2
Order By: Relevance
“…Compared to subjective sleep results which tended to consistently report evidence of poor sleep quality, group difference findings using objective sleep measures were mixed. The majority of the selected studies used PSG as their objective sleep measure, and only two studies employed actigraphy. Most of the studies (10/15) that utilized PSG only used a single night recording.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to subjective sleep results which tended to consistently report evidence of poor sleep quality, group difference findings using objective sleep measures were mixed. The majority of the selected studies used PSG as their objective sleep measure, and only two studies employed actigraphy. Most of the studies (10/15) that utilized PSG only used a single night recording.…”
Section: Resultsmentioning
confidence: 99%
“…44 Therefore, an ambient lighting intervention designed to increase circadian entrainment and improve sleep can also impact populations beyond those studied in the present paper.…”
Section: Discussionmentioning
confidence: 97%
“…For example, gastroesophageal reflux disease (GERD) patients experimentally deprived of sleep have more severe oesophageal symptoms when exposed to acid stimulation protocols . Specific to functional GI disorders, a recent study in women ( n = 24) with IBS showed that self‐reported sleep disturbances were associated with abdominal pain, anxiety and fatigue the next day . Furthermore, since affective disorders (anxiety and depression) are common in IBS, and that sleep disturbances are a hallmark feature of these mood disorders, psychiatric comorbidity may play an important role in understanding the effect of sleep on IBS symptoms.…”
Section: Introductionmentioning
confidence: 99%